Muscle strengthening exercises during pregnancy are associated with increased energy and reduced fatigue. (2nd April 2016) - Ward-Ritacco, Christie; Poudevigne, Mélanie S.; O'Connor, Patrick J.
Abstract: Introduction : Physical inactivity likely contributes to fatigue and low energy during pregnancy but whether acute resistance exercise attenuates these symptoms is unknown. Methods : Twenty-six women performed six low-to-moderate intensity resistance exercises twice per week from weeks 23 to 35 of pregnancy and measurements were made before and after each workout using the Mental and Physical State Energy and Fatigue Scales. Results : Acute resistance exercise usually increased perceived physical and mental energy (92% to 96% of workouts, respectively). These increases did not differ significantly across the 24 exercise sessions for feelings of physical energy or mental energy, even after adjusting for variations in attendance (median = 22/24 workouts). Acute resistance exercise usually decreased perceived physical and mental fatigue (79% to 88% of workouts, respectively), and ANCOVA showed these decreases did not differ significantly across the 24 exercise sessions for feelings of physical fatigue or mental fatigue even after adjusting for variations in attendance. Discussion : The results suggest acute, low-to-moderate intensity muscle strengthening exercise during pregnancy is effective for transiently improving feelings of energy and fatigue.